Fidyah Puasa Ramadhan Menurut Imam Syafi'i - Juaini (Sekolah Tinggi Agama Islam Sumatera Medan, 2018)
The obligation of fasting for a full month in Ramadan begins only in the second year of the Hijri. Fasting is imposed on Muslims who are intelligent, not menstruating, and also not postpartum by doing it confidently for a full month during Ramadan. However, based on the Qur'an, al-Baqarah verse 184 there is the word fidyah, which is to feed a poor person, explaining the existence of rukhsah which God gives to certain people. This verse is disputed by the commentators. There are those who argue that Allah Almighty gives an alternative for people who are obliged to fast, who break the fast intentionally. There are also those who argue that this verse speaks of travelers and sick people, namely for these two groups there are two possibilities: travelers and people who feel heavy to fast, then when they have to break the fast; and there are also those who are essentially able to fast, but are reluctant because they are unwell and / or on a trip, so they are allowed to break the fast if they pay fidyah